Features of intracranial interictal epileptiform discharges associated with memory encoding. (5th September 2021) - Quon, Robert J.; Camp, Edward J.; Meisenhelter, Stephen; Song, Yinchen; Steimel, Sarah A.; Testorf, Markus E.; Andrew, Angeline S.; Gross, Robert E.; Lega, Bradley C.; Sperling, Michael R.; Kahana, Michael J.; Jobst, Barbara C.
Abstract: Objective: Interictal epileptiform discharges (IEDs) were shown to be associated with cognitive impairment in persons with epilepsy. Previous studies indicated that IED rate, location, timing, and spatial relation to the seizure onset zone could predict an IED's impact on memory encoding and retrieval if they occurred in lateral temporal, mesial temporal, or parietal regions. In this study, we explore the influence that other IED properties (e.g., amplitude, duration, white matter classification) have on memory performance. We were specifically interested in investigating the influence that lateral temporal IEDs have on memory encoding. Methods: Two hundred sixty‐one subjects with medication‐refractory epilepsy undergoing intracranial electroencephalographic monitoring performed multiple sessions of a delayed free‐recall task ( n  = 671). Generalized linear mixed models were utilized to examine the relationship between IED properties and memory performance. Results: We found that increased IED rate, IEDs propagating in white matter, and IEDs localized to the left middle temporal region were associated with poorer memory performance. For lateral temporal IEDs, we observed a significant interaction between IED white matter categorization and amplitude, where IEDs with an increased amplitude and white matter propagation were associated with reduced memory performance. Additionally, changes in alpha power after an IED showed a significant positive correlation with memory performance. Significance: Our results suggest that IED properties may be useful for predicting the impact an IED has on memory encoding. We provide an essential step toward understanding pathological versus potentially beneficial interictal epileptiform activity.